DETERMINATION OF ANTHROPOMETRIC CHARACTERISTICS AND MAXIMUM CONSUMPTION OF OXYGEN OF COSTA RICAN PROFESSIONAL CYCLISTS BY AREA OF EXPERTISE AND TYPE OF RACE - Ramos Méndez, Harold; Murillo Murillo, María Alejandra; Sánchez-Ureña, Braulio; Carpio Rivera, Elizabeth; Araya Ramírez, Felipe (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2018)
The purpose of this study was to determine anthropometric characteristics and the maximum consumption of oxygen (VO2max) of professional Costa Rican cyclists. A total of 22 cyclists participated with an average age of 24.7 ± 3.7 years, a body weight of 64.5 ± 2.7 kg, height of 1.73 ± 0.02 m and competition experience of 10 ± 2.3 years. The following were the variables used: weight, height, body fat percentage and VO2max, which was measured directly. Data obtained was analyzed through descriptive statistics (averages and standard deviation), t-student for independent groups and one-way ANOVA with Tukey post hoc. No significant statistical differences were recorded in the following variables: weight (t(20)=0.24; p=.82), height (t(20)=1.37; p=.19), body fat percentage (t(20)=0.90; p=.38) and VO2max (t(20)=0.03; p=.98) among the cyclists that only do road cycling and those who do both road and MTB, depending on the type of race. On the analysis by area of expertise, significant differences were detected only in body weight (F(2,21)=4.95; p=.02) showing that time trialists are significantly heavier than climbers. Conclusion: anthropometric and cardiorespiratory characteristics by type of race and area of expertise of Costa Rican cyclists are similar, except for body weight, which was significantly greater in time trialists than climbers.